Sustainable Development: Divergences And Complexities In Interpretation - Mazloomi, Mehrdad; Hassan, Ahmad Sanusi (2008)

(untitled)
Unprecedented complexities in confronting economy, society and environment in addition to myriad of systematic dysfunctions resulted in UN sponsored World Commission of Environmental Development (WCED) led by former Norwegian Prime Minister Brundtland in 1987.